Cansados de guerra: um estudo clínico sobre a co-autoria na violência familiar - Levy, Suzanna Amarante (2006)
Family violence is the theme of this work. The aim is to investigate how problems or situations experienced by families can facilitate co-authorship in family violence. The following questions were addressed: How is a relationship pattern with violence built in a family? Are the family traumas present in the co-construction of family violence? Besides the traumas, what other situations experienced by families collaborate in developing this relationship pattern? A clinical, qualitative research is carried out where the researcher/therapist studies the system of family violence based on clinical family work with three low-income families. Constructivism and the systemic theory serve as a basis for understanding the family system and for analyses and interpretations of the categories and sub-categories. The results point to intergenerational patterns, difficulties in communication and a lack of reflection as the generators and preservers of violence in the family. Some stressors are considered facilitators, and not determiners of family violence: misery, drugs, deaths, traumas, prejudice, separations, new family arrangements and changes in the life-cycle. Also included as facilitators are the social context, for its permissiveness and impunity, as well as public policies which collaborate in social exclusion. Thus, this work emphasizes the interplay between the individual, family and social systems as co-authors in family violence